Spelling Problems and Teaching Strategies for Student Teachers at a South African University - Vincent Ndishunwani Demana (Journal of English Language Teaching and Linguistics, 2025)
Spelling competence is critical in academic writing, particularly for English student teachers who are expected to serve as role models of accurate language use in their future classrooms. At the South African university, many Level One English Student Teachers enter higher education with spelling challenges that affect both their academic performance and professional identity. This study investigates spelling problems and effective teaching strategies to overcome the problem. Employing a qualitative research approach, the study collected data through classroom observations, semi-structured interviews with lecturers, focus group discussions with students, and analysis of students’ written work. The findings revealed that spelling challenges were mainly influenced by phonological interference from learners’ home languages, limited familiarity with written English, and inadequate prior instruction in spelling rules. Effective interventions identified in the study include explicit spelling instruction, phonics-based approaches, fostering morphological awareness, peer-assisted learning, and the integration of digital tools. The study recommends incorporating structured spelling instruction into English Education modules to enhance student teachers’ writing accuracy, build their professional confidence, and equip them with the skills needed to teach spelling effectively in South African schools.